Pengaruh Current Ratio, Total Asset Turnover, Debt To Equity Ratio, Return On Asset Dan Earning Per Share Terhadap Nilai Perusahaan - Silvia Indrarini; Marcellina Gelanicya Berdikari Jayanti (Universitas Katolik Widya Karya Malang, 2023)
This study aims to determine the effect of the current ratio, total asset turnover, debt to equity ratio, return on assets and earnings per share on the value of building construction companies listed on the Indonesia Stock Exchange for the period 2016 – 2020. This type of research is explanatory research. The study population was 18 companies, the sample was selected using purposive sampling method, 7 companies were selected. The analysis technique uses descriptive statistical tests, classical assumption tests, multiple linear regression tests and hypothesis testing. The results of the simultaneous analysis of the current ratio, total asset turnover, debt to equity ratio, return on assets and earnings per share affect firm value. Current ratio has a significant negative effect on firm value, while total asset turnover, debt to equity ratio, return on assets and earnings per share have no effect and are not significant on firm value. The variable that has the most dominant influence on firm value is the current ratio.